Inhibitory Activities of Zygophyllum album: A Natural Weight-Lowering Plant on Key Enzymes in High-Fat Diet-Fed Rats. (8th November 2012) - Mnafgui, Kais; Hamden, Khaled; Ben Salah, Hichem; Kchaou, Mouna; Nasri, Mbarek; Slama, Sadok; Derbali, Fatma; Allouche, Noureddine; Elfeki, Abdelfattah
Abstract : Obesity is a serious health problem that increased risk for many complications, including diabetes and cardiovascular disease. The results showed EZA, which found rich in flavonoids and phenolic compounds, exhibited an inhibitory activity on pancreatic lipase in vitro with IC50 of 91.07 μ g/mL. In vivo administration of this extract to HFD-rats lowered body weight and serum leptin level; and inhibited lipase activity of obese rats by 37% leading to notable decrease of T-Ch, TGs and LDL-c levels accompanied with an increase in HDL-c concentration in serum and liver of EZA treated HFD-rats. Moreover, the findings revealed that EZA helped to protect liver tissue from the appearance of fatty cysts. Interestingly, supplementation of EZA modulated key enzyme related to hypertension such as ACE by 36% in serum of HFD animals and improve some of serum electrolytes such as Na +, K +, Cl −, Ca 2+ and Mg 2+ . Moreover, EZA significantly protected the liver-kidney function by reverted back near to normal the values of the liver-kidney dysfunction indices AST&ALT, ALP, CPK and GGT activities, decreased T-Bili, creat, urea and uric acid rates. In conclusion, these results showed a strong antihypelipidemic effect of EZA which can delay the occurrence of dislipidemia and hypertension.